Sustainable Hop Production in the Mountainous Region of Rio de Janeiro, Brazil: Agroindustrial Waste-Based Bokashi Fertilization Enhances Yield and Soil Quality - Silva, Leonardo Lopes da; Guerra , José Guilherme Marinho; Assis , Renato Linhares de; Rouws, Janaina Ribeiro Costa; Antunes, Luiz Fernando de Sousa; Aquino , Adriana Maria de (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
Hop (Humulus lupulus L.), a climbing species of the Cannabaceae family, is a key crop for the brewing industry. This fast-growing plant can reach heights of seven meters within 90 days of regrowth, demanding substantial nutrient inputs due to its high biomass accumulation. In Brazil, research on hop nutrition remains limited, necessitating studies on sustainable fertilization strategies. This study evaluated the effects of fertilization with a fermented compost (bokashi) formulated from brewers’ spent grain and castor bean meal on hop production components and soil chemical properties under organic management. The experiment tested five compost doses (0, 2, 4, 8, and 16 Mg ha-1) in a randomized block design. Results revealed linear increases in P, K, and Mg concentrations in the 0–20 cm soil layer with higher compost doses. Leaf tissue analysis showed elevated K, Zn, and Mn levels, proportional to application rates. For yield components, the highest dose (16 Mg ha⁻¹) achieved optimal performance: 639.13 cones plant-1 and 0.51 kg of fresh biomass plant-1. While the compost delivered significant nutrient inputs, hop yields did not reach maximum potential, suggesting the need for higher dosage trials.